IMPLEMENTATION OF E-SERVICE QUALITY METHOD AND IMPORTANCE PERFORMANCE ANALYSIS (IPA) FOR SERVICE QUALITY ANALYSIS ON WATTPAD APPLICATION - Raja, Arta Novrida Lumban; Utomo, Rio Guntur (JIPI (Jurnal Ilmiah Penelitian dan Pembelajaran Informatika), 2025)
Everyday life now requires mobile applications. One popular application is Wattpad, an online platform that allows users to read, write, and share stories for free, though some are also paid. With millions of users worldwide, Wattpad has become a trendy place for writers and readers to interact and enjoy literary works. However, with the rapid growth of Wattpad users, application managers need to ensure the quality of service they provide to users. This research involved 402 respondents who are active users of the Wattpad application. Given the importance of service quality in maintaining Wattpad's competitiveness in a competitive market and enhancing the user experience, this study applies the Importance of Performance Analysis (IPA) and E-Service Quality methods. Site Organization, Responsiveness, Reliability, User Friendliness, Personal Needs, and Efficiency are the six variables used to measure user perceptions. After data was collected through the distribution of questionnaires to Wattpad users, the data was analyzed using SPSS. The analysis results show that the level of user satisfaction with the services offered by the Wattpad application reaches 85%